Sovpadanje družbenih dilem in mimikrije v Odiseji - Smrke, Marjan (Teorija in praksa, 2020)
In this article, we identify and analyse social dilemmas and mimicry in Homer's The Odyssey. We focus on cases of intersection between social dilemmas and mimicry. Most of them appear as two cognitively complex activities: strategic procrastination/delay (as a solution to mostly an intrapersonal social dilemma) and identity mimicry or the mimicry of emotions and intentions. We also explore and discover indicative resemblances and differences with The Iliad in this respect. The reading of epics from antiquity is not without relevance for our time (of reflexive modernity). We discover and comment on the connections between certain themes in The Odyssey and the global ecological crisis and with mimicry in the digital era. Some defectors who pretend (using digital signals) to be cooperating on solving the ecological crisis are exposed
Keywords: Adaptacija; Adaptation; Človekovo vedenje; Družbena mimikrija; družbene dileme; Human behavior; Odiseja; Social mimicry; strateško prokrastiniranje; tragedija skupnega